Pengembangan Masyarakat Berbasis Kewirausahaan untuk Meningkatkan Pariwisata dan Budaya di Desa Wisata Kandri Kota Semarang - Andi Hallang Lewa (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2018)
Entrepreneurship-based community development to improve tourism and culture in Kandri tourism village Semarang is one form of activity in the economic field by empowering the tourism village community. Kandri Tourism Village has a special agenda in the field of culture which is one of the efforts in preserving the culture in the village including wayang suket, ketoprak, art lesung and jathilan. Along with the increase of visitors both domestic and foreign tourists so that there is a need for entrepreneurship development in Kandri Tourism Village so that later it can improve the standard of living in the economic field, especially for the people in Kandri Tourism Village. In making tourism village development successful, strategic efforts that need to be developed include: human resource development, profitable partnerships, village government activities, tourism promotion activities, village festivals, village community organization development, collaboration with universities. Entrepreneurship development in a village tourism certainly requires the cooperation and infrastructure that supports tourism activities in Kandri village including eco-lodge, eco-recreation, eco-education, eco-research, eco-energy, eco-development, and eco-promotion. Some forms of entrepreneurship that can be developed in Kandri tourism villages include being a tour guide, providing culinary services, providing accommodation, making tour packages, providing transportation to and from Kandri tourism villages, providing typical village souvenirs.